Tribunal of Arbitration under treaty and convention between Great Britain and the United States of America relating to Behring Sea; third draft for case [electronic resource]. - Bering Sea Tribunal of Arbitration. ([S.l. : s.n.)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 14442-14448. Caption title. Electronic reproduction. Mode of access: Internet. 44